Effect of the Re-Emergence of Militancy on Small and Medium Enterprises (SMES) in the Niger Delta Region of Nigeria - F. M. Attah; G. E. Anagbogu; F. E. Ojong; G. E. Odinka; D. C. Enamhe; A. M. Ogabo Agba; A. I. Akintola; Pius U. Angioha; V. O. Ogunsola (ARRUS Journal of Social Sciences and Humanities, 2023)
Small and medium scale enterprises are the forces that help in the development of any economy and society at large. As such, any threat to its operations will impact negatively on society. In the Niger Delta region, the re-emergence of militancy has had dire consequence on the living standard of the people. Though, there have been studies on insecurity and its impact on SMEs elsewhere, however, none have really looked at the effect of the re-emergence of militancy on small and medium scale enterprises in the Niger Delta region of Nigeria. The rear absence of studies on this topic justifies the relevance of this study. Consequently, the study is designed to investigate among others, the effect of the re-emergence of militancy on small and medium enterprises in the Niger Delta region of Nigeria. The results of the study provide a better understanding of the impact the Niger Delta militant has on SMEs in the region, the extent to which the costs of re-emergence identified are present in the study. The findings suggest that SMEs especially the oil and gas related businesses, and petite traders in the Niger Delta have suffered from both direct and indirect costs of the militant such as kidnapping, bombing, assassination, robbery, and road blocking. The lack of alignment of militant interests by programme leaders explains why some beneficiaries have returned to insurgency in the Niger Delta Region. Therefore, for post amnesty programme, there is need to strengthen the legitimacy of the leadership through better management, openness and accountability, monitoring and coordination, lowering the expense of governance, and putting ex-militants' interests at the forefront of concerns are all needed to increase the legitimacy of the leadership